Geological atlas of Africa : with notes on stratigraphy, tectonics, economic geology, geohazards and geosites of each country - Schlüter, Thomas (Springer, 2008)
Attempts to summarise the geology of Africa by presenting it in an atlas, and to synthesize the stratigraphy, tectonics, economic geology, geohazards, geosites and geoscientific education of each country and territory of the continent. This atlas aims to contribute to capacity building in African Earth Sciences.